Beyond the four varnas : the untouchables in India - Mukherjee, Prabhati (Shimla, 1988)
Who were the untouchables in India? Why and when did they become so? are some of the questions the present study attempts to answer. As the sage proceeds, from the Rgveda onward, it unfold various facets of the problem faced by these people. 'Who were the untouchables in India?', and 'Why and when did they become so?" are some of the questions the present study attempts to answer. As the saga proceeds, from the Rgveda onward, it unfolds various facets of the problem faced by these people. The main focus of the study is on the role of the 'Aryans' in India around ca. 400 B.C. to A.D. 200, when significant changes took place in society. From about this time the exact Sanskrit word for 'untouchable' began to appear in the sacred texts, replacing the words like 'impure', 'unclean', etc. This was the first identification of untouchables as a marginal group, living the mercy of the predominant 'Aryans' and being used as and when necessary. This narrative of emergence of untouchability in India is profusely documented, and substantiates how indology combined with anthropology and sociology can make a meaningful contribution to understanding social reality.
Keywords: Sociology